Effect of dulaglutide in promoting abstinence during smoking cessation: a single-centre, randomized, double-blind, placebo-controlled, parallel group trial. (March 2023) - Lengsfeld, Sophia; Burkard, Thilo; Meienberg, Andrea; Jeanloz, Nica; Vukajlovic, Tanja; Bologna, Katja; Steinmetz, Michelle; Bathelt, Cemile; Sailer, Clara O.; Vogt, Deborah R.; Hemkens, Lars G.; Speich, Benjamin; et al.
Summary: Background: Quitting smoking is difficult due to barriers such as craving for cigarettes and post-cessation weight gain. Recent experimental data suggest a role of glucagon-like peptide-1 (GLP-1) in the pathophysiology of addiction in addition to appetite regulation and weight control. We hypothesized that a pharmacological intervention with the GLP-1 analogue dulaglutide during smoking cessation may improve abstinence rates and reduce post-cessation weight gain. Methods: This is a single-centre, randomized, double-blind, placebo-controlled, parallel group, superiority study conducted in the University Hospital Basel in Switzerland. We included adult smokers with at least moderate cigarette dependence who wanted to quit. Participants were randomly assigned to a 12-week treatment with dulaglutide 1.5 mg once weekly or placebo subcutaneously in addition to standard of care including behavioural counselling and oral varenicline pharmacotherapy of 2 mg/day. The primary outcome was self-reported and biochemically confirmed point prevalence abstinence rate at week 12. Secondary outcomes included post-cessation weight, glucose metabolism, and craving for smoking. All participants who received one dose of study drug were included in the primary and safety analyses. The trial was registered on ClinicalTrials.gov (NCT03204396 ). Findings: Between June 22, 2017, and December 3, 2020, 255 participants were enrolled and randomly assigned to each group (127 in the dulaglutide group and 128 in the placebo group). After 12 weeks, 63% (80/127) participants on dulaglutide and 65% (83/128) on placebo treatment were abstinent (difference in proportions −1.9% [95% Confidence interval (CI) −10.7, 14.4], p-value (p) = 0.859). Dulaglutide decreased post-cessation weight (−1 kg [standard deviation (SD) 2.7]), while weight increased on placebo (+1.9 kg [SD 2.4]). The baseline-adjusted difference in weight change between groups was −2.9 kg (95% CI −3.59,  −2.3, p < 0.001). Haemoglobin A1c (HbA1c) level declined on dulaglutide treatment (baseline-adjusted median difference in HbA1c between groups −0.25% [interquartile range (IQR) −0.36,  −0.14], p < 0.001). Craving for smoking declined during treatment without any difference between the groups. Treatment-emergent gastrointestinal symptoms were very common in both groups: 90% (114/127) of participants on dulaglutide and 81% (81/128) on placebo). Interpretation: Dulaglutide had no effect on abstinence rates but prevented post-cessation weight gain and decreased HbA1c levels. GLP-1 analogues may play a role in future cessation therapy targeting metabolic parameters such as weight and glucose metabolism. Funding: Swiss National Science Foundation, the Gottfried Julia Bangerter-Rhyner Foundation, the Goldschmidt-Jacobson Foundation, the Hemmi-Foundation, the University of Basel, the Swiss Academy of Medical Sciences .